Boy : tales of childhood - Dahl, Roald, 1916-1990; Blake, Quentin (New York : Puffin Books, 2013)
Presents humorous anecdotes from the author's childhood which includes summer vacations in Norway and an English boarding school.
Goodbye school
Originally published: Farrar, Straus & Giroux,1984.
Keywords: Dahl, Roald -- Childhood and youth; Authors, English -- 20th century -- Biography